Kymissala : archaeology - education - sustainability - Stephanakēs, Manolēs I., (Archaeopress Publishing Ltd, 2018)
Kymissala, on the southwest coast of Rhodes, is an area of great archaeological interest. Here, after ten years of systematic research, in terms of archaeology, education and sustainable development, 14 original studies are presented, constituting the first complete presentation of the area of Kymissala and the work in progress.